TINJAUAN SISTEMATIS: FAKTOR-FAKTOR YANG MEMPENGARUHI KESIAPAN KERJA - Feneta Fidi Kirani; Ahmad Chusairi (Jurnal Abdi Insani, 2022)
Job readiness can be defined as the degree to which a graduate is perceived to have the attitudes and attributes that make them ready to enter or they are ready to succeed in the work environment. The purpose of this literature study is to understand what factors indicate the dynamics of work readiness in individuals who will work so that they can provide benefits and efforts to increase work readiness. Search for literature used in research. This is taken from 3 journal databases, namely Garuda Dikti, SAGE & Science Direct by limiting the year the article was published for the last 5 years from 2017-2021. After going through the search and screening process with inclusion and exclusion criteria, it was found (N=7) seven research articles in this literature study. The results of this literature study indicate that the factors related to job readiness are personal factors, environmental factors, and educational factors. Personal factors are related to how the dynamics are psychologically, interests, talents, and motivations in individuals. External factors are related to the support of people around, knowledge, information and interaction with significant others such as parents, peers, teachers, etc. The educational factor is related to learning opportunities, gaining knowledge and opportunities to practice / go directly to the field. Thus, graduates who will enter the world of work can optimize their abilities during their education by following various skills according to their field of work later. Then the graduates can develop motivation in themselves as individuals who will be ready to work and get good support from the environment and people around them. This research can be a reference for job seekers in growing their readiness to look for work, as well as for readers to be able to identify what factors are needed in work, and can also be used by companies or employers as reference material in accepting workers.